Comparison of some of the physical properties of wood charcoal produced in a double barrel method with wood charcoal produced in the traditional method of the residue of (Olea spp). - خليل, علاء; أسامة رضوان , (Latakia University Journal -Biological Sciences Series, 2023)
This research was carried out during the season 2019 and 2020 in Tartous -Safita, which aimed to comparing some physical properties of wood charcoal produced by the double-barrel method and the traditional method of pruning residues of olive trees. The experiment was designed using two gastric barrels of different size and diameter, the largest with a volume of 200 liters and a diameter of 60 cm, fully open on one side and closed on the other side to represent the outer barrel. The exterior is closed on one side and open on the other side. The physical and apparent properties of the resulting coal were studied. The double drums method outperformed the traditional method in terms of the weight and yield of the charcoal produced by 25% compared to 20% in the traditional method, and the double drums method outperformed the traditional method in terms of the time of the charring process, as the charring process took from (4-2) hours compared to( 4 -3) days in the traditional way. The results were close between the two methods in the time of start of ignition and the time of complete ignition, which was a little longer in the traditional method, while the extinguishing time was 1.94 minutes longer with coal produced by the barrel method compared to the traditional method. The results also shoed that the coal produced by the traditional method has a specifc heat capacity greater than that of the double barrel method, which amounted to (0.55-0.52) respectively, but burning temperate was bigger in the double barrel.